Penerapan Teori Antrian pada Pelayanan Teller Bank BNI Kantor Cabang Pembantu Air Tawar - Windy Septia Putri; Defri Ahmad (Journal of Mathematics UNP, 2020)
Abstract– Queuing is one of the problems that is often faced by public services, as happened at the BNI Sub-Branch Office Air Tawar. It is due to the large number of customers who come to get services. This paper discusses the resolution of the problem faced by obtaining a queuing model that is applied to bank tellers. Data collection is carried out for 5 days (Monday to Friday, at 09.00 - 12.00 Western Indonesian Time) and is done through interviews and direct observations at the teller section of the BNI Sub-Branch Office Air Tawar. Based on the results of the analysis by measuring the performance of the queuing system, it is found that the model applied is .The arrival time of the customer is Poisson distribution and the time of service to the costumer is exponential distribution. The general discipline used is first in first out (FIFO). The basic queuing model is the Multiple Channel Queuing System.Keywords– Queue Theory, Multiple Channel Queuing System.